The Meaning and Scope of Personal Data under the Singapore Data Protection Act - CHIK, Warren B. (Institutional Knowledge at Singapore Management University, 2014)
It is important to examine and determine the meaning of “personal data” as it is the subject matter of the Singapore Data Protection regime. What constitutes “personal data” determines the scope of the Personal Data Protection Act. Although it is defined under the Act, the experience in other jurisdictions has shown that the elements of that (and other forms of ) definition can still give rise to some difficulty in its application to specific cases. In this paper, the authors aim to provide some guidance and recommendations for the interpretation of “personal data” within the context of legislative intent and objective.